Composição da comunidade de artrópodes associada a copa de Calophyllum brasiliense (Guttiferae) no Pantanal, Mato Grosso, Brasil - Marque, M. I.; Adis, J.; Battirola, L. D.; Brescovit, A. D.; Silva, F. H. O.; Silva, J. L. (Amazoniana, 2007)
One tree each of Calophyllum brasiliense CAMBESS. (Guttiferae) was surveyed during low water (October 2000) and high water (February 2001) to analyze the seasonal variation in composition and structure of the associated arthropod communities.
Keywords: Guttiferae